Czy w okresie wczesnego cesarstwa Kreta była gospodarczymi peryferiami świata grecko-rzymskiego? - Łoś, Andrzej (Instytut Historyczny Uniwersytetu Wrocławskiego, 2023)
This paper considers relationship between massive exports of wine and changes to the structure of the Cretan economy. During the early imperial period the production and trade of wine constituted a major component of the economy of Crete. There is, however, a controversy about the start of exports of insular wines. Some archaeological evidence challenged previous arguments that the production and trade of Cretan wine did not begin until the reign of Augustus, but this evidence is not unequivocal. It is certain that the golden age of Cretan wine reached its peak during the Flavian and Antonine periods when exports to the rest of Europe, first of all to Italy, were truly massive. The development of the wine trade changed the economic landscape of Crete. The Island under the Principate was one of the most developed regions of the Roman Empire.
Keywords: Kreta; Kampania; Rzym; wino; produkcja; handel; eksport; gospodarka